How do southern Spaniards create the conditions necessary to initiate negotiations with strangers? - Villemoes, Anette (HERMES - Journal of Language and Communication in Business, 2003)
Based on focus group discussions and interviews with Spanish-speaking business people experienced in negotiations with Spaniards this paper focuses on what they say about their first time business meetings with southern Spaniards. The informants include both non-Spaniards and Spaniards, the last group comprising both Spaniards from the northern and the southern parts of Spain. Thus foreigners and northern Spaniards talk about their experience related to first time business meetings with southern Spaniards, whereas the southern Spaniards reflect on how they see themselves in first time meetings with business people from other parts of Spain and from abroad. Special attention is given to how the informants describe the start-up phase of their business relations. The paper introduces different theoretical approaches to such first time intercultural meetings – including a sociological approach, the approach offered by intercultural communication, and Face theory - and based on the key concepts of these approaches the paper discusses to what extent the businessmen involved draw on concepts related to the theories in their sense-making effort.